High-voltage fuse ceramic tube material and preparation method thereof
By combining modified graphite and ceramic materials, high-voltage fuse ceramic tube materials with high toughness and reduced brittleness are prepared, which solves the problem of high brittleness of ceramic tube materials and improves the fracture toughness of the material.
Patent Information
- Application Number
- CN202411944284.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-03-25
AI Technical Summary
Ceramic tube material is highly brittle and is easily damaged when subjected to external forces, affecting the normal use of the fuse.
Modified graphite is prepared by using graphite oxide and KH560 as raw materials, and ball milling and calcining with materials such as modifiers, quartz sand and PVA to form a ceramic tube material containing a cage structure and metal titanium doped, and boron nitride is deposited on the surface.
It enhances the toughness of ceramic pipes, reduces brittleness, improves fracture toughness, can effectively withstand loads during fracture, and dissipate more fracture energy.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of ceramic material preparation, and in particular to a high-voltage fuse ceramic tube material and a preparation method thereof. Background Art
[0002] The function of a fuse is the same as that of a fuse. When the circuit current is abnormal and exceeds its rated current, it will melt and protect the circuit. The fuse will melt the fuse itself and disconnect the circuit from the heat generated by itself. Fuses are widely used in high and low voltage power distribution systems and control systems as well as electrical equipment. As a short circuit and overcurrent protector, it is one of the most commonly used protection devices. As a type of fuse, the fuse of a tubular fuse is installed in the fuse body. At present, the fuse body is mostly made of glass or ceramic. Since the mechanical strength of ceramic is far superior to that of glass, ceramic fuses have gradually become the mainstream. However, ceramics are brittle and are easily damaged when subjected to external forces, which affects the normal use of fuses. Summary of the invention
[0003] The purpose of the present invention is to provide a high-voltage fuse ceramic tube material and a preparation method thereof, which solves the problem of high brittleness of ceramic tube materials at present.
[0004] The purpose of the present invention can be achieved through the following technical solutions: A method for preparing a high-voltage fuse ceramic tube material specifically comprises the following steps: Step A1: Graphite oxide, KH560, triphenylphosphine and DMF are mixed evenly, and reacted for 2-3 hours at a speed of 120-150 r / min and a temperature of 120-130° C. to obtain modified graphite; modifier, modified graphite, dimethyldiethoxysilane, methyltriethoxysilane and DMF are mixed evenly, and stirred at a speed of 150-200 r / min and a temperature of 65-70° C., and deionized water and hydrochloric acid solution are added to react for 2-3 hours, and then tetrabutyl titanate is added, and the reaction is continued for 2-3 hours, and the temperature is raised to 120-130° C. and the reaction is carried out for 3-5 hours to obtain a precursor; Step A2: The precursor, quartz sand, PVA and ethanol are mixed and ball-milled evenly, and the ethanol is distilled off to obtain a composite material, the composite material is added to a mold, and argon gas is introduced for protection. At a heating rate of 10°C / min, the temperature is increased to 210-220°C, and the mixture is calcined for 1-1.5h, and the temperature is increased to 1300-1400°C, and the mixture is calcined for 2-3h to obtain a green body. The green body is deposited for 1-1.5h at an argon flow rate of 100mL / min, a boron trichloride flow rate of 15mL / min, an ammonia flow rate of 50mL / min, a pressure of 7-9kPa, and a temperature of 1000°C to obtain a high-voltage fuse ceramic tube material.
[0005] Furthermore, the molar ratio of the carboxyl group on the graphite oxide described in step A1 to KH560 is 1:1, the amount of triphenylphosphine used is 1% of the mass of KH560, the amount ratio of the modifier, modified graphite, dimethyldiethoxysilane, methyltriethoxysilane, deionized water, hydrochloric acid solution and tetrabutyl titanate is 5g:1g:100mmol:100mmol:150mL:20mL:5mmol, and the mass fraction of the hydrochloric acid solution is 15%.
[0006] Furthermore, the mass ratio of the precursor, quartz sand and PVA described in step A2 is 20:55:5, and the molecular weight of PVA is 2000.
[0007] Further, the modifier is prepared by the following steps: Step B1: Methyltrimethoxysilane, sodium hydroxide, isopropanol and deionized water are mixed evenly, reacted at a speed of 120-150 r / min and a temperature of 85-90° C. for 10-15 hours, isopropanol and deionized water are distilled off, the substrate, triethylamine and tetrahydrofuran are mixed evenly, nitrogen is introduced for protection, at a speed of 150-200 r / min and a temperature of 0° C., methyldichlorosilane is added with stirring, the reaction is carried out for 3-5 hours, the temperature is raised to 20-25° C., and the reaction is carried out for 20-25 hours to obtain dihydrogen cage-type silsesquioxane.
[0008] Step B2: Mix dihydrogen cage silsesquioxane, p-hydroxystyrene, chloroplatinic acid and toluene, introduce nitrogen protection, and react for 20-25 hours at a speed of 60-80 r / min and a temperature of 80-85° C. to obtain a modified monomer; mix phenol, 3-chloropropyltrimethoxysilane, triethylamine and toluene, introduce nitrogen protection, and react for 6-8 hours at a speed of 200-300 r / min and a temperature of 50-60° C. to obtain a functional monomer; Step B3: Evenly mix the functional monomer, the modified monomer, the phenol and the formaldehyde solution, stir and add ammonia water to adjust the pH value to 8-8.5 at a speed of 150-200 r / min and a temperature of 70-75°C, react for 1-1.5 hours, heat to 95-98°C, react for 1-1.5 hours, and obtain a modifier.
[0009] Furthermore, the amount ratio of methyltrimethoxysilane, sodium hydroxide, isopropanol and deionized water in step B1 is 120mmol:80mmol:120mL:2.5mL, and the amount ratio of substrate, triethylamine, tetrahydrofuran and methyldichlorosilane is 12g:5g:30mL:3.5g.
[0010] Furthermore, the molar ratio of the dihydrogen cage silsesquioxane and p-hydroxystyrene described in step B2 is 1:2, the amount of chloroplatinic acid used is 1‰ of the mass of p-hydroxystyrene, and the molar ratio of phenol, 3-chloropropyltrimethoxysilane and triethylamine is 1:1:1.2.
[0011] Furthermore, the amount ratio of the functional monomer, the modified monomer, the phenol and the formaldehyde solution in step B3 is 1 mmol:4 mmol:20 mmol:5 mL, and the mass fraction of the formaldehyde solution is 18%.
[0012] Beneficial effects of the present invention: A high-voltage fuse ceramic tube material prepared by the present invention uses graphite oxide and KH560 as raw materials, so that the carboxyl group on the graphene oxide reacts with the epoxy group on the KH560 to obtain modified graphite, and the modifier, modified graphite, dimethyldiethoxysilane, methyltriethoxysilane and tetrabutyl titanate are hydrolyzed and condensed to obtain a precursor, and the precursor, quartz sand and PVA are ball-milled and mixed and roasted to obtain a green body, and then a deposition treatment is performed on the surface of the green body so that the surface of the ligand is coated with boron nitride to obtain a ceramic tube material; The modifier is hydrolyzed with methyltrimethoxysilane as a raw material to generate a sodium silanol structure, and then under the action of triethylamine, the sodium silanol reacts with the chlorine atom site on methyldichlorosilane to obtain a dihydrogen cage silsesquioxane, dihydroxy cage silsesquioxane reacts with p-hydroxystyrene, so that the Si-H bond on the dihydroxy cage silsesquioxane reacts with the double bond on the p-hydroxystyrene to obtain a modified monomer, phenol reacts with 3-chloropropyltrimethoxysilane, so that the phenolic hydroxyl group on the phenol reacts with the chlorine atom site on the 3-chloropropyltrimethoxysilane to obtain a functional monomer, and the functional monomer, the modified monomer, phenol and formaldehyde solution react to form a phenolic resin structure to obtain a modifier; The ceramic tube material contains a cage structure and metal titanium doping inside, which can enhance the toughness of the ceramic tube material. The graphite structure inside achieves the effect of particle toughening, further reducing the brittleness of the ceramic tube material. At the same time, the surface is coated with boron nitride, which can deflect the crack to bear the load during fracture, resulting in the dissipation of more fracture energy and improving the toughness of the ceramic tube material. DETAILED DESCRIPTION
[0013] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0014] Embodiment 1: A method for preparing a high-voltage fuse ceramic tube material specifically comprises the following steps: Step A1: Graphite oxide, KH560, triphenylphosphine and DMF are mixed evenly, and reacted at a speed of 120 r / min and a temperature of 120° C. for 2 h to obtain modified graphite; modifier, modified graphite, dimethyldiethoxysilane, methyltriethoxysilane and DMF are mixed evenly, and stirred at a speed of 150 r / min and a temperature of 65° C., and deionized water and hydrochloric acid solution are added to react for 2 h, and then tetrabutyl titanate is added, and the reaction is continued for 2 h, and the temperature is raised to 120° C. and the reaction is carried out for 3 h to obtain a precursor; Step A2: The precursor, quartz sand, PVA and ethanol are mixed and ball-milled evenly, and the ethanol is distilled off to obtain a composite material, the composite material is added into a mold, and argon gas is introduced for protection. The temperature is increased to 210°C at a heating rate of 10°C / min, and the mixture is calcined for 1h, and the temperature is increased to 1300°C and calcined for 2h to obtain a green body. The green body is deposited for 1h at an argon flow rate of 100mL / min, a boron trichloride flow rate of 15mL / min, an ammonia flow rate of 50mL / min, a pressure of 7kPa, and a temperature of 1000°C to obtain a high-voltage fuse ceramic tube material.
[0015] The molar ratio of carboxyl groups on the graphite oxide described in step A1 to KH560 is 1:1, the amount of triphenylphosphine used is 1% of the mass of KH560, the amount ratio of modifier, modified graphite, dimethyldiethoxysilane, methyltriethoxysilane, deionized water, hydrochloric acid solution and tetrabutyl titanate is 5g:1g:100mmol:100mmol:150mL:20mL:5mmol, and the mass fraction of hydrochloric acid solution is 15%.
[0016] The mass ratio of the precursor, quartz sand and PVA described in step A2 is 20:55:5, and the molecular weight of PVA is 2000.
[0017] The modifier is prepared by the following steps: Step B1: Mix methyltrimethoxysilane, sodium hydroxide, isopropanol and deionized water evenly, react at a speed of 120 r / min and a temperature of 85°C for 10 hours, distill off the isopropanol and deionized water, mix the substrate, triethylamine and tetrahydrofuran evenly, introduce nitrogen protection, stir and add methyldichlorosilane at a speed of 150 r / min and a temperature of 0°C, react for 3 hours, heat to 20°C, and react for 20 hours to obtain dihydrogen cage-type silsesquioxane.
[0018] Step B2: Dihydrogen cage silsesquioxane, p-hydroxystyrene, chloroplatinic acid and toluene are mixed evenly, nitrogen is introduced for protection, and the reaction is carried out for 20 hours at a speed of 60 r / min and a temperature of 80° C. to obtain a modified monomer; phenol, 3-chloropropyltrimethoxysilane, triethylamine and toluene are mixed, nitrogen is introduced for protection, and the reaction is carried out for 6 hours at a speed of 200 r / min and a temperature of 50° C. to obtain a functional monomer; Step B3: Evenly mix the functional monomer, modified monomer, phenol and formaldehyde solution, stir and add ammonia water to adjust the pH value to 8 at a speed of 150 r / min and a temperature of 70°C, react for 1 hour, heat to 95°C, and react for 1 hour to obtain a modifier.
[0019] The amount ratio of methyltrimethoxysilane, sodium hydroxide, isopropanol and deionized water in step B1 is 120mmol:80mmol:120mL:2.5mL, and the amount ratio of substrate, triethylamine, tetrahydrofuran and methyldichlorosilane is 12g:5g:30mL:3.5g.
[0020] The molar ratio of the dihydrogen cage silsesquioxane and p-hydroxystyrene described in step B2 is 1:2, the amount of chloroplatinic acid used is 1‰ of the mass of p-hydroxystyrene, and the molar ratio of phenol, 3-chloropropyltrimethoxysilane and triethylamine is 1:1:1.2.
[0021] The amount ratio of the functional monomer, the modified monomer, the phenol and the formaldehyde solution described in step B3 is 1mmol:4mmol:20mmol:5mL, and the mass fraction of the formaldehyde solution is 18%.
[0022] Embodiment 2: A method for preparing a high-voltage fuse ceramic tube material specifically comprises the following steps: Step A1: Graphite oxide, KH560, triphenylphosphine and DMF are mixed evenly, and reacted at a speed of 120 r / min and a temperature of 125° C. for 3 hours to obtain modified graphite; the modifier, modified graphite, dimethyldiethoxysilane, methyltriethoxysilane and DMF are mixed evenly, and stirred at a speed of 200 r / min and a temperature of 65° C., and deionized water and hydrochloric acid solution are added to react for 2 hours, and then tetrabutyl titanate is added, and the reaction is continued for 3 hours, and the temperature is raised to 125° C. and the reaction is carried out for 4 hours to obtain a precursor; Step A2: The precursor, quartz sand, PVA and ethanol are mixed and ball-milled evenly, and the ethanol is distilled off to obtain a composite material. The composite material is added into a mold, and argon gas is introduced for protection. The temperature is increased to 220°C at a heating rate of 10°C / min, and the mixture is calcined for 1.5 hours. The temperature is increased to 1300°C and the mixture is calcined for 3 hours to obtain a green body. The green body is deposited for 1.5 hours at an argon flow rate of 100 mL / min, a boron trichloride flow rate of 15 mL / min, an ammonia flow rate of 50 mL / min, a pressure of 8 kPa, and a temperature of 1000°C to obtain a high-voltage fuse ceramic tube material.
[0023] The molar ratio of carboxyl groups on the graphite oxide described in step A1 to KH560 is 1:1, the amount of triphenylphosphine used is 1% of the mass of KH560, the amount ratio of modifier, modified graphite, dimethyldiethoxysilane, methyltriethoxysilane, deionized water, hydrochloric acid solution and tetrabutyl titanate is 5g:1g:100mmol:100mmol:150mL:20mL:5mmol, and the mass fraction of hydrochloric acid solution is 15%.
[0024] The mass ratio of the precursor, quartz sand and PVA described in step A2 is 20:55:5, and the molecular weight of PVA is 2000.
[0025] The modifier is prepared by the following steps: Step B1: Methyltrimethoxysilane, sodium hydroxide, isopropanol and deionized water are mixed evenly, and reacted at a speed of 120 r / min and a temperature of 90°C for 10 hours, and the isopropanol and deionized water are distilled off. The substrate, triethylamine and tetrahydrofuran are mixed evenly, and nitrogen is introduced for protection. At a speed of 200 r / min and a temperature of 0°C, methyldichlorosilane is added with stirring, and the reaction is carried out for 4 hours. The temperature is raised to 25°C and the reaction is carried out for 20 hours to obtain dihydrogen cage-type silsesquioxane.
[0026] Step B2: Dihydrogen cage silsesquioxane, p-hydroxystyrene, chloroplatinic acid and toluene are mixed evenly, nitrogen is introduced for protection, and the reaction is carried out for 20 hours at a speed of 60 r / min and a temperature of 85° C. to obtain a modified monomer; phenol, 3-chloropropyltrimethoxysilane, triethylamine and toluene are mixed, nitrogen is introduced for protection, and the reaction is carried out for 7 hours at a speed of 300 r / min and a temperature of 55° C. to obtain a functional monomer; Step B3: Evenly mix the functional monomer, modified monomer, phenol and formaldehyde solution, stir and add ammonia water to adjust the pH value to 8.5 at a speed of 150 r / min and a temperature of 73°C, react for 1.5 hours, heat to 95°C, and react for 1.5 hours to obtain a modifier.
[0027] The amount ratio of methyltrimethoxysilane, sodium hydroxide, isopropanol and deionized water in step B1 is 120mmol:80mmol:120mL:2.5mL, and the amount ratio of substrate, triethylamine, tetrahydrofuran and methyldichlorosilane is 12g:5g:30mL:3.5g.
[0028] The molar ratio of the dihydrogen cage silsesquioxane and p-hydroxystyrene described in step B2 is 1:2, the amount of chloroplatinic acid used is 1‰ of the mass of p-hydroxystyrene, and the molar ratio of phenol, 3-chloropropyltrimethoxysilane and triethylamine is 1:1:1.2.
[0029] The amount ratio of the functional monomer, the modified monomer, the phenol and the formaldehyde solution described in step B3 is 1mmol:4mmol:20mmol:5mL, and the mass fraction of the formaldehyde solution is 18%.
[0030] Embodiment 3: A method for preparing a high-voltage fuse ceramic tube material specifically comprises the following steps: Step A1: Graphite oxide, KH560, triphenylphosphine and DMF are mixed evenly, and reacted at a speed of 150 r / min and a temperature of 130° C. for 3 hours to obtain modified graphite; modifier, modified graphite, dimethyldiethoxysilane, methyltriethoxysilane and DMF are mixed evenly, and stirred at a speed of 200 r / min and a temperature of 70° C., and deionized water and hydrochloric acid solution are added to react for 3 hours, and then tetrabutyl titanate is added, and the reaction is continued for 3 hours, and the temperature is raised to 130° C. and the reaction is carried out for 5 hours to obtain a precursor; Step A2: The precursor, quartz sand, PVA and ethanol are mixed and ball-milled evenly, and the ethanol is distilled off to obtain a composite material. The composite material is added into a mold, and argon gas is introduced for protection. The temperature is increased to 220°C at a heating rate of 10°C / min, and the mixture is calcined for 1.5 hours. The temperature is increased to 1400°C and the mixture is calcined for 3 hours to obtain a green body. The green body is deposited for 1.5 hours at an argon flow rate of 100 mL / min, a boron trichloride flow rate of 15 mL / min, an ammonia flow rate of 50 mL / min, a pressure of 9 kPa, and a temperature of 1000°C to obtain a high-voltage fuse ceramic tube material.
[0031] The molar ratio of carboxyl groups on the graphite oxide described in step A1 to KH560 is 1:1, the amount of triphenylphosphine used is 1% of the mass of KH560, the amount ratio of modifier, modified graphite, dimethyldiethoxysilane, methyltriethoxysilane, deionized water, hydrochloric acid solution and tetrabutyl titanate is 5g:1g:100mmol:100mmol:150mL:20mL:5mmol, and the mass fraction of hydrochloric acid solution is 15%.
[0032] The mass ratio of the precursor, quartz sand and PVA described in step A2 is 20:55:5, and the molecular weight of PVA is 2000.
[0033] The modifier is prepared by the following steps: Step B1: Methyltrimethoxysilane, sodium hydroxide, isopropanol and deionized water are mixed evenly, and reacted at a speed of 150 r / min and a temperature of 90°C for 15 hours, and the isopropanol and deionized water are distilled off. The substrate, triethylamine and tetrahydrofuran are mixed evenly, and nitrogen is introduced for protection. At a speed of 200 r / min and a temperature of 0°C, methyldichlorosilane is added with stirring, and the reaction is carried out for 5 hours. The temperature is raised to 25°C and the reaction is carried out for 25 hours to obtain dihydrogen cage-type silsesquioxane.
[0034] Step B2: Dihydrogen cage silsesquioxane, p-hydroxystyrene, chloroplatinic acid and toluene are mixed evenly, nitrogen is introduced for protection, and the reaction is carried out for 25 hours at a speed of 80 r / min and a temperature of 85° C. to obtain a modified monomer; phenol, 3-chloropropyltrimethoxysilane, triethylamine and toluene are mixed, nitrogen is introduced for protection, and the reaction is carried out for 8 hours at a speed of 300 r / min and a temperature of 60° C. to obtain a functional monomer; Step B3: Evenly mix the functional monomer, modified monomer, phenol and formaldehyde solution, stir at a speed of 200 r / min and a temperature of 75°C, add ammonia water to adjust the pH value to 8.5, react for 1.5 hours, heat to 98°C, and react for 1.5 hours to obtain a modifier.
[0035] The amount ratio of methyltrimethoxysilane, sodium hydroxide, isopropanol and deionized water in step B1 is 120mmol:80mmol:120mL:2.5mL, and the amount ratio of substrate, triethylamine, tetrahydrofuran and methyldichlorosilane is 12g:5g:30mL:3.5g.
[0036] The molar ratio of the dihydrogen cage silsesquioxane and p-hydroxystyrene described in step B2 is 1:2, the amount of chloroplatinic acid used is 1‰ of the mass of p-hydroxystyrene, and the molar ratio of phenol, 3-chloropropyltrimethoxysilane and triethylamine is 1:1:1.2.
[0037] The amount ratio of the functional monomer, the modified monomer, the phenol and the formaldehyde solution described in step B3 is 1mmol:4mmol:20mmol:5mL, and the mass fraction of the formaldehyde solution is 18%.
[0038] Comparative Example 1: Compared with Example 1, no modified graphite was added in this comparative example, and the remaining steps were the same.
[0039] Comparative Example 2: Compared with Example 1, tetrabutyl titanate was not added in this comparative example, and the remaining steps were the same.
[0040] Comparative Example 3: Compared with Example 1, no modified monomer was added in this comparative example, and the remaining steps were the same.
[0041] Comparative Example 4: Compared with Example 1, no functional monomer was added in this comparative example, and the remaining steps were the same.
[0042] The ceramic tube materials prepared in Examples 1-3 and Comparative Examples 1-4 were tested according to GB / T6569-2006 standard, with a sample size of 40 mm×4 mm×3 mm, a span of 30 mm on a universal testing machine, and a test rate of 0.5 mm / min for bending strength. The fracture toughness was tested under the conditions of a cut depth of 2 mm, a cut width of 0.2 mm, a span of 15 mm, and a pressure head loading rate of 0.05 mm / min. The test results are shown in the following table; ; It can be seen from the above table that this application has good toughness.
[0043] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the concept of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.
Claims
1. A method for preparing a high-voltage fuse ceramic tube material, characterized in that: The specific steps include: Step A1: Graphite oxide, KH560, triphenylphosphine and DMF are mixed and reacted to obtain modified graphite, the modifier, modified graphite, dimethyldiethoxysilane, methyltriethoxysilane and DMF are mixed and stirred, and deionized water and hydrochloric acid solution are added, and after the reaction, tetrabutyl titanate is added and the reaction is continued to obtain a precursor; Step A2: ball-mill the precursor, quartz sand, PVA and ethanol evenly, distill and remove the ethanol to obtain a composite material, add the composite material into a mold, pass argon gas for protection, and calcine to obtain a green body, and deposit the green body in an atmosphere of argon, boron trichloride and ammonia to obtain a high-voltage fuse ceramic tube material.
2. The method for preparing a high voltage fuse ceramic tube material according to claim 1, characterized in that: The molar ratio of carboxyl groups on the graphite oxide described in step A1 to KH560 is 1:1, and the usage ratio of the modifier, modified graphite, dimethyldiethoxysilane, methyltriethoxysilane, deionized water, hydrochloric acid solution and tetrabutyl titanate is 5g:1g:100mmol:100mmol:150mL:20mL:5mmol.
3. The method for preparing a high voltage fuse ceramic tube material according to claim 1, characterized in that: The mass ratio of the precursor, quartz sand and PVA described in step A2 is 20:55:
5.
4. The method for preparing a high voltage fuse ceramic tube material according to claim 1, characterized in that: The modifier is prepared by the following steps: Step B1: methyltrimethoxysilane, sodium hydroxide, isopropanol and deionized water are mixed for reaction, the isopropanol and deionized water are removed by distillation, the substrate, triethylamine and tetrahydrofuran are mixed evenly, nitrogen is introduced for protection, methyldichlorosilane is added after stirring, and a reaction is carried out to obtain dihydrogen cage-type silsesquioxane; Step B2: mixing dihydrogen cage silsesquioxane, p-hydroxystyrene, chloroplatinic acid and toluene uniformly, introducing nitrogen protection, and reacting to obtain a modified monomer; mixing phenol, 3-chloropropyltrimethoxysilane, triethylamine and toluene, introducing nitrogen protection, and reacting to obtain a functional monomer; Step B3: The functional monomer, the modified monomer, phenol and the formaldehyde solution are mixed and stirred and ammonia water is added to react to obtain a modifier.
5. The method for preparing a high voltage fuse ceramic tube material according to claim 4, characterized in that: The amount ratio of methyltrimethoxysilane, sodium hydroxide, isopropanol and deionized water in step B1 is 120mmol:80mmol:120mL:2.5mL, and the amount ratio of substrate, triethylamine, tetrahydrofuran and methyldichlorosilane is 12g:5g:30mL:3.5g.
6. The method for preparing a high voltage fuse ceramic tube material according to claim 4, characterized in that: The molar ratio of the dihydrogen cage silsesquioxane and p-hydroxystyrene described in step B2 is 1:2, and the molar ratio of phenol, 3-chloropropyltrimethoxysilane and triethylamine is 1:1:1.
2.
7. The method for preparing a high voltage fuse ceramic tube material according to claim 4, characterized in that: The amount ratio of the functional monomer, modified monomer, phenol and formaldehyde solution described in step B3 is 1mmol:4mmol:20mmol:5mL.
8. A high voltage fuse ceramic tube material, characterized in that: Prepared according to any one of claims 1 to 7.